Hydroxysafflor Yellow A Protects Against Myocardial Ischemia/Reperfusion Injury via Suppressing NLRP3 Inflammasome and Activating Autophagy - Ye, Jingxue; Lu, Shan; Wang, Min; Ge, Wenxiu; Liu, Haitao; Qi, Yaodong; Fu, Jianhua; Zhang, Qiong; Zhang, Bengang; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2020)
Myocardial ischemia/reperfusion (MI/R) injury is a serious threat to human health. Hydroxysafflor yellow A (HSYA), the main water-soluble ingredient extracted from Carthami flos (Carthamus tinctorius L.), has therapeutic potential for treating MI/R injury. However, the mechanisms of HSYA‑mediated protection from MI/R injury are incompletely understood. In the present study, we investigated the effects and the underlying mechanisms of HSYA during MI/R. Adult Sprague-Dawley rats were subjected to left anterior descending artery ligation for 30 min followed by 24 h of reperfusion with or without HSYA treatment. The protective effect of HSYA was detected by 2,3,5-triphenyl tetrazolium chloride (TTC) staining, hematoxylin eosin (HE) staining, and myocardial enzymes detections. Serum levels of inflammatory factors such as TNF-α, IL-1β, and IL-18, were detected using ELISA kits. The expression of NLRP3 and other related proteins in the myocardium was detected by western blot and immunohistochemistry. The expression of autophagy-related proteins, including Atg5, BECN1, P62, and LC3B, was detected by western blot to evaluate the effect of HSYA on autophagy. Results showed that HSYA decreased the myocardial infarct size and attenuated the cardiac dysfunction in rats after I/R. In addition, HSYA inhibited myocardial apoptosis compared with the I/R group, decreased the levels of inflammatory cytokines in rat serum, reduced NLRP3 inflammasome expression, and induced autophagy. Mechanistically, our results demonstrated that HSYA can activate AMPK to improve autophagy and inhibit NLRP3 inflammasome by inhibiting the mTOR pathway. This work provides strong data supporting for the clinical applications of HSYA in MI/R injury.